Factors affecting evidence-use in food policy-making processes in health and agriculture in Fiji - Waqa, Gade (BMC Public Health, 2017)
BACKGROUND: There is limited research on the use of evidence to inform policy-making in the Pacific. This study aims to identify and describe factors that facilitate or limit the use of evidence in food-related policy-making in the Health and Agriculture Ministries in Fiji. METHODS: Semi-structured face-to-face interviews were conducted with selected policy-makers in two government ministries that were instrumental in the development of food-related policies in Fiji designed to prevent Non-Communicable Diseases (NCDs). Snowball sampling was used to recruit, as key informants, senior policy-makers in management positions such as national advisors and directors who were based at either the national headquarters or equivalent. Interviewees were asked about their experiences in developing food-related or other policies, barriers or facilitators encountered in the policy development and implementation process and the use of evidence. Each interview lasted approximately 45–60 minutes, and was conducted in English. Audio-recorded interviews were transcribed, thematically coded and analyzed using N-Vivo 8.0 software. RESULTS: Thirty-one policy-makers from the Ministry of Health and Medical Services (MoHMS n = 18) and the Ministry of Agriculture (MoA n = 13) in Fiji participated in the study. Whilst evidence is sometimes used in food-related policy-making in both the Health and Agriculture Ministries (including formal evidence such as published research and informal evidence such as personal experiences and opinions), it is not yet embedded as an essential part of the process. Participants indicated that a lack of resources, poor technical support in terms of training, the absence of clear strategies for improving competent use of evidence, procedures regarding engagement with other stakeholders across sectors, varying support from senior managers and limited consultation across sectors were barriers to evidence use. The willingness of organizations to create a culture of using evidence was reported as a facilitator. CONCLUSION: The use of evidence in policy-making will only become a reality in Fiji if it is a formalized part of the government’s policy-making systems. A systems approach to food-related policy-making and implementation may achieve this by helping Ministries manage the complex and dynamic nature of food-related policy-making in Fiji.